PXF-1 promotes synapse development at the neuromuscular junction in Caenorhabditis elegans - Lamb, Reagan; Dhar, Bithika; Cherra, Salvatore J. (Frontiers in Molecular Neuroscience, 2022)
Guanine nucleotide exchange factors (GEFs) are a family of proteins that modulate small G protein signaling. Mutations in a subfamily of GEFs that act on Rap, known as RapGEFs, have been associated with neurological disorders, and knockout mice display impairments in neuronal activity. However, the precise functions of RapGEFs in the nervous system remain unclear. Here, we have used the Caenorhabditis elegans neuromuscular junction, to investigate how the RapGEF homolog, PXF-1, regulates synaptic function. We found that loss of function mutations in pxf-1 reduced cholinergic activity at the neuromuscular junction. We observed that PXF-1 is expressed in the nervous system, and its expression in neurons is sufficient to promote synaptic activity. In pxf-1 mutant animals, there is a reduction in the levels of synaptic vesicles in cholinergic motor neurons but no change in the overall synapse numbers. In addition to synaptic vesicles proteins, we also found that filamentous actin, a scaffold for nascent synapses, was reduced at developing cholinergic synapses in pxf-1 mutant animals. Our studies indicate that PXF-1 regulates neuromuscular function by promoting the formation of actin filaments to support the development of motor neuron synapses.